2020
DOI: 10.1021/acssuschemeng.0c02854
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Relithiation for Direct Regeneration of LiCoO2 Materials from Spent Lithium-Ion Battery Electrodes

Abstract: Increased generation of spent lithium-ion batteries (LIBs) has driven the exploration of new methods for reusing and/or recycling LiCoO2 cathode materials. Herein, an electrochemical relithiation method was proposed to directly regenerate LiCoO2 cathode materials using the waste Li x CoO2 electrode as a base. It was shown that Li+ was successfully inserted into the waste Li x CoO2 electrode, and this relithiation process became faster with either a higher Li2SO4 concentration or a higher cathodic current densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 46 publications
2
105
0
Order By: Relevance
“…It has been shown that using silicon nanotubes instead of nanowires is more effective. In nanotubes, the necessary space is provided for volume change on both sides of the inner and outer walls [34,[59][60][61]. In addition, nanotubes are usually thinner than nanowires, so transmitters are better, because silicon is a semiconductor and is also amorphous during the duty cycle due to stresses, it does not conduct well electronically during the duty cycle [47,48,54].…”
Section: Different Nano Morphologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that using silicon nanotubes instead of nanowires is more effective. In nanotubes, the necessary space is provided for volume change on both sides of the inner and outer walls [34,[59][60][61]. In addition, nanotubes are usually thinner than nanowires, so transmitters are better, because silicon is a semiconductor and is also amorphous during the duty cycle due to stresses, it does not conduct well electronically during the duty cycle [47,48,54].…”
Section: Different Nano Morphologiesmentioning
confidence: 99%
“…Another way to solve the problem is hollow nanostructures. In this method, the necessary empty space is provided during the entry and exit of lithium through a hollow volume [26,27,33,58,59]. The finite element method shows that in the same volume, the hollow structure undergoes less stress during the work cycle, so they have better resistance to the crushing phenomenon (Fig.…”
Section: Different Nano Morphologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,[9][10][11][12][13][14][15] However, the processes are often complicated with several steps and utilize concen-published. [33][34][35] Zhang et al, [33] for example, have recently shown that the re-lithiation of Li x CoO 2 electrode is possible without removing the active material from the current collector foil. However, in all these studies, LiCoO 2 was at some point removed from the current collector.…”
Section: Introductionmentioning
confidence: 99%